Graphene and carbon nanotubes activate different cell surface receptors on macrophages before and after deactivation of endotoxins. Issue 11 (9th May 2017) - Lahiani, Mohamed H.; Gokulan, Kuppan; Williams, Katherine; Khodakovskaya, Mariya V.; Khare, Sangeeta
Abstract: Nanomaterial synthesis and handling in a non‐sterile environment can result in the final product becoming contaminated with bacterial endotoxin or lipopolysaccharides (LPB). During toxicological testing, the effects caused by endotoxin‐contaminated nanomaterials can be misinterpreted in the end‐point analysis (such as cytotoxicity and immune responses) and could result in erroneous conclusions. The objective of this study was twofold: (i) to test different carbon‐based nanomaterials (CBNs) [pristine graphene and multi‐wall carbon nanotubes (MWCNTs)] for the presence of endotoxin and develop strategies for depyrogenation, and (ii) to compare the immune response exhibited by macrophages after exposure to native CBNs versus depyrogenated CBNs. The gel‐clot limulus amebocyte lysate (LAL) and chromogenic‐based LAL assays were used to detect endotoxins. Results revealed that the CBNs contained greater amounts of endotoxin than are approved by major regulatory agencies (0.5 EU ml −1 ). Three repeated cycles of autoclaving reduced the endotoxin in the test materials. Macrophages were incubated with pyrogenated and depyrogenated pristine graphene and MWCNTs to test differences in phagocytosis, cytotoxicity, and expression of genes involved in macrophage activation. The uptake of depyrogenated CBNs was significantly reduced as compared with pyrogenated CBNs. Exposure of macrophages to depyrogenated CBNs resulted in a distinct pattern of gene expression for TLR signaling, NOD‐like receptor signaling, and downstream signal transduction molecules. Furthermore, macrophages exposed to both types of CBNs showed the downregulation of TLR5 and NLRC4 inflammasomes. The results of this study reaffirm that assessment of endotoxin and other bacterial contamination is critical when evaluating the cellular toxicity of nanomaterials. Published 2017. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Published 2017. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Abstract : Here we show that commercially available nanomaterials could contain endotoxins. Carbon‐based nanomaterials (CBNs) tend to interact with endotoxins and interfere with the results of detection using the chromogenic‐based LAL assays. Finally, we compared the immune‐response of macrophages to pyrogenated and de‐pyrogenated graphene and multi‐walled carbon nanotubes.